2010
DOI: 10.1111/j.1365-2109.2010.02499.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity in various coastal mariculture ponds in Southeast China and in diseased eels as revealed by culture and culture-independent molecular techniques

Abstract: Mariculture ponds are widely distributed in Chinese coasts and have become a threat to the health of coastal ecosystems. In order to improve our understanding on the microbial composition in mariculture environments, we sampled a variety of ponds farming different animals or plants around the Dongshan Island and Xiamen Island in Southeast China and isolated cultures from the tissues of diseased eels. Analysis by polymerase chain reaction (PCR)-denaturing gradient gel electrophoresis (DGGE), clone library and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…The discrepancy determined in the bacterial community analysed by culturedependent and culture-independent methods in the present study is a finding that previously has been reported in various ecosystems (Tamaki et al, 2005;Michaud et al, 2009;Huang et al, 2010;Zeng et al, 2010;Szabo et al, 2011). By using culture-dependent methods to analyze the bacterial community of an ecosystem, it is widely recognized that only 0.001 to 15% of the total cell counts can be cultured (Amann et al, 1995).…”
Section: Discussionmentioning
confidence: 44%
“…The discrepancy determined in the bacterial community analysed by culturedependent and culture-independent methods in the present study is a finding that previously has been reported in various ecosystems (Tamaki et al, 2005;Michaud et al, 2009;Huang et al, 2010;Zeng et al, 2010;Szabo et al, 2011). By using culture-dependent methods to analyze the bacterial community of an ecosystem, it is widely recognized that only 0.001 to 15% of the total cell counts can be cultured (Amann et al, 1995).…”
Section: Discussionmentioning
confidence: 44%
“…During the past few decades many articles have been published in which the bacteria of aquatic environments were identified by culture-dependent and culture-independent techniques (Arias et al 2006;AlHarbi & Uddin 2008;Huang et al 2008;Zeng et al 2010;Niu et al 2011). Nevertheless, the cultured species account for less than 5% of the total bacteria in environmental samples (Amann et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the cultured species account for less than 5% of the total bacteria in environmental samples (Amann et al 1995). Recently, a geneclone-library-based culture-independent technique has been frequently used to determine the complex microbial community in natural aquatic environments (Arias et al 2006;Huang et al 2008;Zeng et al 2010;Niu et al 2011), because it provides more information on bacterial diversity than culture-dependent and some of culture-independent techniques. However, to our knowledge, previous studies have not used culture-independent techniques to investigate 728 J.Q.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations